Susan Howe’s Caesurae - Andrew Eastman (Association Française d'Etudes Américaines, 2021)
Readings of Susan Howe’s visual poetry tend to focus on how she uses the space of the page to act on language, through an opposition, then, between the visual and the textual. This paper argues that Howe’s works are specified precisely by the way they obscure the line between what is and is not linguistic. The paper looks into the ways in which Susan Howe’s poems, specifically in her recent collection Debths, depend on and work with the line unit, use and abuse our sense that poems appear in typographic lines. Three examples from Debths look at problems raised by the various ways in which Howe scissors the line, arguing that the line is a place where something happens to language, a frame for a caesura, a space where a silence can take place—as seen in the book’s title. Syntax and its caesuring then “make” the line, a line which works as a way of intimating voice, exploring the interstices of language and body.